Mechanical behavior and fatigue failure analysis of standing seam aluminum alloy roof system under temperature effect - Wang, Mingming; Ou, Tong; Xin, Zhiyong; Wang, Dayang; Zhang, Yongshan (Journal of Building Engineering, 2021)
Standing seam metal roof systems with universal high-strength, lightweight, and thin-walled characteristics have been applied worldwide in massive large-span landmark buildings, such as gymnasiums, airports, and railway stations. The existing research focuses on the wind uplift design, but there are few studies on the mechanical properties under the temperature effect. In this paper, the temperature effect of the standing seam aluminum alloy roof (SSAAR) system was studied. To be familiar with the mechanical and deformation characteristics of the SSAAR system, the static loading tests under different temperatures and boundary constraints were carried out. Two specimens, one with anti-wind clips and the other without anti-wind clips, were further tested under cyclic loading to evaluate and quantify the fatigue failure characteristics of the roof system. The testing results indicate that the stress concentration, thermal expansion displacement, and wear of the SSAAR system are significant. The slab rib stress is the largest, accounting for about 83.7% of the yield strength, followed by the slab surface stress, and the slab bottom stress is the smallest. The horizontal displacement is greater than the vertical displacement, and the maximum is about 20.42 mm. The boundary constraint mainly affects the support stress and vertical displacement to increase by 47.2% and 79.3% respectively. The anti-wind clips mainly increase the wear thickness of the roof slab, which is increased by 67.5%. •The stress concentration and thermal expansion displacement of the SSAAR system are significant.•The slab rib stress is the largest, followed by the slab surface stress, and the slab bottom stress is the smallest.•The horizontal displacement is greater than the vertical displacement.•The wear thickness of the roof slab is larger than that of support.